The outbreak of rhinoceros beetle (Oryctes rhinoceros) in oil palm at selected oil palm plantations / Muhammad Shakir Zakaria - Zakaria, Muhammad Shakir (Faculty of Plantation and Agrotechnology, 2018)
Oryctes rhinoceros also known as rhinoceros beetle and the most important pest cause huge damage on selected oil palm crop in plantation area. This study aims to generate useful information about the population rhinoceros beetle and their ecology in order to help farmers in reducing of population and huge losses on the oil palm crop that caused by rhinoceros beetle in their field. The objectives of the study were to determine the abundance of rhinoceros beetle over a year in replanting, immature and mature at selected oil palm plantations and evaluate the related factors that affect the population of rhinoceros beetle. Thus study started from 5th August 2017 until 30th October 2017 and was carried out in Parit Jawa, Batu Pahat and Tangkak, Johor and required 11 samples of pheromone traps. As a result, comparison between graph showed that Tangkak area have greater amount of beetle compared to another area. However, there was no significant differece between population of rhinoceros beetle in immature and mature (P-value=0.671>0.05). In addition, the result for the mature and replanting (P-value=0.071>0.05) still showed there was no significant difference. Moreover, the comparisons number of rhinoceros beetle between in immature and mature oil palms showed there was significant different (P<0.05). While, the lowest number of beetle population is at immature area or Batu Pahat, Johor. All the result show that all beetle population is fluctuate but still not achieve threshold level. The results indicate that replanting site can cause high population of beetle and need take care more seriously to avoid the production of oil palm became lowered.